Analisis Faktor yang Mempengaruhi Kesuksesan Usaha pada Pedagang Handphone Sepanjang Jalan Moses Yogyakarta. - Suhartini, Yati (Universitas PGRI Yogyakarta, 2016)
The research was carried out to find the influence of five business location factors such as rent expense, infrastructure, business environment, consumer, and security on the success of the mobile phone business a long Jalan Moses, Yogyakarta. The respondents of the research were all of the handphone traders a long Jalan Moses, as many as 81 respondents. The data was derived from a survey and collected by applying question-naires, and analyzed by using multiple linear regressions. This research indicated that factors of rent expense, infrastructure, business environment, consumer, and security, all together showed a significant influence on the business success. These were indicated by the value of F amounting to 24,132 with the significance level of 0,000, where as R square counting to 0,591. The regression coefficient of each factor of rent expense, infrastructure, business environment, consumer, and security toward business success are 0,368 (X1); 0,294 (X2); 0,399(X3); 0,311 (X4); 0,394 (X5); and the significant level of each factor are 0,003; 0,031, 0,007, 0,031, and 0,020 respectively.